Travels in the Interior of Africa - Park, Mungo (Wordsworth Editions Ltd, 2002)
In 1795 Mungo park, A Twenty four year old scottish surgeon,set out from the Gambia to trace the course of the Niger,a river which Europeans had no first hand knowledge.
Keywords: Classics-Africa-Travels-Discovery and exploration-Non fiction